2018
DOI: 10.4274/jcp.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Traditional Beliefs, and Practices of Mothers with 0-24 Month-Old Children Concerning Child Care

Abstract: GİRİŞ ve AMAÇ: Geleneksel uygulamalar, modernleşen tıp uygulamalarına karşın güncelliğini korumaktadır. Bu araştırmanın amacı 0-24 aylık çocuğu olan annelerin çocuk bakımına ilişkin bilgi, geleneksel inanç ve uygulamalarını belirlemektir.YÖNTEM ve GEREÇLER: Tanımlayıcı özellikte olan bu araştırma Erzincan il merkezinde bulunan beş Aile Sağlığı Merkezine Ekim 2014-Şubat 2015 tarihleri arasında herhangi bir nedenle başvuran 0-24 aylık bebeği olan araştırmaya alınma ölçütlerini karşılayan 207 anne ile yapıldı. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Diarrhea is one of the most common medical disorders for which CAM is used [ 11 , 34 ]. The literature has shown that parents commonly utilize various CAM modalities such as potato, yoghurt, banana, mint-lemon, coffee, and cola to manage diarrhea in their children [ 35 , 36 ]. The result of the present study regarding the use of honey for diarrhea may have arisen because the research questions did not include other traditional methods but only queried the use of honey.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is one of the most common medical disorders for which CAM is used [ 11 , 34 ]. The literature has shown that parents commonly utilize various CAM modalities such as potato, yoghurt, banana, mint-lemon, coffee, and cola to manage diarrhea in their children [ 35 , 36 ]. The result of the present study regarding the use of honey for diarrhea may have arisen because the research questions did not include other traditional methods but only queried the use of honey.…”
Section: Discussionmentioning
confidence: 99%